Transrectal Absorber Guide Raster‐Scanning Optoacoustic Mesoscopy for Label‐Free In Vivo Assessment of Colitis - Adrian Buehler; Emma Brown; Lars‐Philip Paulus; Markus Eckstein; Oana‐Maria Thoma; Mariam‐Eleni Oraiopoulou; Ulrich Rother; André Hoerning; Arndt Hartmann; Markus F. Neurath; Joachim Woelfle; Oliver Friedrich; et al. (Advanced Science, 2023)
Abstract Optoacoustic imaging (OAI) enables microscale imaging of endogenous chromophores such as hemoglobin at significantly higher penetration depths compared to other optical imaging technologies. Raster‐scanning optoacoustic mesoscopy (RSOM) has recently been shown to identify superficial microvascular changes associated with human skin pathologies. In animal models, the imaging depth afforded by RSOM can enable entirely new capabilities for noninvasive imaging of vascular structures in the gastrointestinal tract, but exact localization of intra‐abdominal organs is still elusive. Herein the development and application of a novel transrectal absorber guide for RSOM (TAG‐RSOM) is presented to enable accurate transabdominal localization and assessment of colonic vascular networks in vivo. The potential of TAG‐RSOM is demonstrated through application during mild and severe acute colitis in mice. TAG‐RSOM enables visualization of transmural vascular networks, with changes in colon wall thickness, blood volume, and OAI signal intensities corresponding to colitis‐associated inflammatory changes. These findings suggest TAG‐RSOM can provide a novel monitoring tool in preclinical IBD models, refining animal procedures and underlines the capabilities of such technologies to address inflammatory bowel diseases in humans.